How can we help?

You can also find more resources in our Help Center.

x = 5

3x - 7 = 8

x = -5

-3x - 7 = 8

x = ⁻½

6x + 2 = -1

x = -7

-4x + 6 = 34

x = -10

-4x - 6 = 34

x = 7

4x + 6 = 34

x = 10

4x - 6 = 34

x = 10

-43 = 7 - 5x

x = -10

-43 = 7 + 5x

x = 6

-40 = 8 - 8x

x = -4

-4x - 1 = 15

x = 35

x/5 + 3 = 10

x = -22

-x/2 - 8 = 3

x = -77

x/7 + 14 = 3

x = 2

7 - x = 5

x = -9

-5 - x = 4

x = -4

-3x - 5 = 7

x = -6

6x + 16 = -20

x = -7

x/7 - 5 = -6

x = -2

-6x + 2 = 14

x = -5

-3x - 7 = 8

x = -5

9 - x = 14

x = 2

-½x - 3 = -4